Transforming peasants, property and power : the collectivization of agriculture in Romania, 1949-1962 - Iordachi, Constantin; Dobrincu, Dorin, 1972- (Central European University Press, 2009)
The subject matter of the volume is part of larger research agenda on the process of land collectivization in the former communist camp, focusing on state, identity and property. The main innovation of the volume is to apply recent interdisciplinary approaches to the study of the collectivization process, asking what types of new peasant-state relations it formed and how it transformed notions of self, persons, and things (such as land). The project conceived of changes in the system of ownership as causing changes in the identity and attitude of people; similarly, it regarded the study of personal identities as essential for understanding changes in the system of ownership. This perspective is rare in the area-studies approaches to the topic. Unlike other works on the subject, the volume treats the entire history of the campaign of collectivization in Romania, between 1949 and 1962. It also fully covered Romania's territory, with at least two researchers in every historical province. Since the process of collectivization varied across space and time, the participants to the volume selected a broad sample of research sites differing in religious and ethnic composition, economy, terrain, date of collectivization, and other related variables. Several of the project participants focused on national-level policies and practices (i.e., property legislation, and debates about the form collectivization should take); the others conducted case studies, working across a broad span of communities and experiences.